Molecular Imaging of Glial Tumors: Established and Emerging Tracers - Dev, Indraja D.; Rangarajan, Venkatesh; Purandare, Nilendu C.; Puranik, Ameya D. (Indian Journal of Neurosurgery, 2023)
Various positron emission tomography (PET) tracers have been developed and extensively studied in the field of neuro-oncology imaging. In the management of brain tumors, accurate delineation of tumor extent, assessment of treatment response, and detection of early recurrence are the most important factors. At present, conventional anatomical imaging paired with amino acid tracer PET imaging is the recommended imaging modality for glial tumor evaluation. Newer PET tracers targeting various structures in the tumor microenvironment have been extensively studied. This review summarizes the established and emerging PET tracers having potential impact on neuro-oncology practice.
Keywords: FDG; FET; FDOPA; PET/CT; glioma